Pengaruh Kompensasi, Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan Rajaklana Resto dan SPA - Hanum Indriati, Inayat; Ratna Ningrum, Natalia; Endra Saputra, Koko (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
This research aims to determine the effect of compensation, work discipline and job satisfaction on the performance of Rajaklana Resto and Spa employees. The research was carried out from October 2022 to March 2023. This research is quantitative research with a total of 65 respondents and the sampling technique used saturated sampling technique. Data collection was carried out by interviews and questionnaires. The analysis technique uses multiple linear regression analysis with the help of SPSS 22.0 for Windows. The results of this research show that all variables have a positive and significant influence on employee performance. Compensation, work discipline and job satisfaction simultaneously have a significant effect on performance as evidenced by the F test results which have a value of 0.598. Compensation, work discipline and job satisfaction on performance amounted to 59.8%, and the remaining 40.2% was influenced by other variables outside this research.